The Dental Reference Manual A Daily Guide for Students and Practitioners - Weinstein, Geraldine M.; Zientz, Mitchell T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is designed to meet the needs of both dental students and dentists by providing succinct and quickly retrievable answers to common dental questions. Students will find both that it clearly presents the particulars which should be familiar to every dentist and that it enables them to see the (3z(Bbig picture(3y (Band contextualize information introduced to them in the future. Practicing dentists, on the other hand, will employ the book as a daily reference to source information on important topics, materials, techniques, and conditions. The book is neither discipline nor specialty specific. The first part is wide ranging and covers the essentials of dental practice while the second part addresses individual specialties and the third is devoted to emergency dental treatment. Whether as a handy resource in the student$1 (Bs backpack or as a readily available tool on the office desk, this reference manual fills an important gap in the dental literature.s
PART 1 Essentials of Dental Practice -- The Comprehensive Head and Neck Exam -- Radiology -- Caries Prevention, Desensitizing and Remineralizing Teeth -- Local Anesthesia Challenges -- Modern Day Treatment Planning Dilemmas: Implants versus Endodontic treatment -- Restorative Considerations for Endodontically Treated Teeth -- Restorative Material Selection for Fixed Prosthesis -- Removable Partial Design -- Occlusion -- Indirect Restorations with CAD/CAM Technology -- Digital Impressions -- PART 2 The Specialties in General Dentistry -- Endodontics -- Periodontics -- Common Lesions in Oral Pathology for the General Dentistry -- Oral Surgery -- Pediatric Dentistry -- Orthodontics -- Implants -- PART 3 References for Everyday Practice -- The Examination, Differential Diagnosis, and Management of Toothache Pain -- Communicating with Dental Laboratories -- Navigating Evidence Based Dentistry -- Common Dental Prescriptions -- Medical Considerations and Emergency Protocols -- PART 4 Pathways of a Dental Career -- Private Practice -- The President$1 (Bs Dentist -- On Building a Dental School -- In pursuit of Dentistry from Zimbabwe!s
Keywords: Dentistry; Oral surgery; Maxillofacial surgery; Dentistry; Dentistry; Oral and Maxillofacial Surgery